Comparison of Ropivacaine alone Versus Ropivacaine with Dexamethasone on the duration of Analgesia in Ultrasound Guided Adductor Canal Block for Arthroscopic Anterior Cruciate Ligament Reconstruction Surgery - Kashif Hussain, Adnan Nawaz, Hafiz Hammad Ul Haq, Ch. Zargham Liaqat, Muhammad Ahmad Khan, Afraz Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Adductor canal block (ACB) has been propounded as best analgesic technique for post-operative pain in knee arthroscopy, especially in ACLR. The goal is to maximise recovery outcomes if adding dexamethasone to ropivacaine in adductor canal blocks for ACL repair improves postoperative pain management. Objectives: To compare mean VAS of ultrasound-guided ACB with ropivacaine alone and ropivacaine with dexamethasone in ACLR for postoperative pain. Methodology: This Randomized Controlled Trial was conducted at Department of Anesthesia in Orthopaedics Unit, Ghurki Trust Teaching Hospital, Lahore during February 04, 2023 to August 10, 2023. After approval of hospital Ethical Review Committee, 264 patients fulfilling inclusion criteria were randomly allocated into two groups using lottery method. First rescue analgesic dose of i.v. injection (inj.) nalbuphine 0.1mg/kg (max 8 mg) administered in case of VAS more than 3. if VAS remains >3, a second rescue analgesic i.e. i.v. inj. ketorolac 30mg was injected. Results: Of 264 patients, 132 were in Group A and 132 were in Group B. In Group A, more than half of cases were females with a mean age of 34.83±9.27 years. In Group B, more than half of cases were males with a mean age of 34.10±9.48 years. The mean postoperative pain was 3.43±.84 in Group A significantly higher than Group B i.e., 2.99±.84 as p<.001. Conclusion: It was concluded that combining dexamethasone with ropivacaine in adductor canal block considerably reduced average pain score compared to ropivacaine alone in anterior cruciate ligament arthroscopic surgery. Keywords: Adductor canal block; Ropivacaine; Dexamethasone; Anterior cruciate ligament reconstruction; Postoperative pain; Visual Analog Scale; Ultrasound-guided block; Randomized controlled trial.